BLENDED LEARNING AS AN INTEGRATED PEDAGOGICAL MECHANISM FOR DEVELOPING PROFESSIONAL COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS - Qilichova Zarifa Xayrullo qizi (International Journal of Literature and Language Studies, 2026)
The digital transformation of higher education has created new requirements for the professional training of future foreign language teachers. Today, professional competence is not limited to linguistic knowledge; it also includes methodological, communicative, digital-pedagogical, reflective and assessment-related abilities. This article examines blended learning as an integrated pedagogical mechanism for developing the professional competence of future foreign language teachers. The study is based on theoretical analysis, pedagogical modelling and the author’s dissertation research on improving the professional competence of future English language teachers through blended learning. The article proposes an integrated framework consisting of four interrelated components: an integrated conceptual model, adaptive blended learning methodology, professional learning ecosystem and Professional Competence Index. The findings show that blended learning becomes pedagogically effective when classroom instruction, online learning, independent study, authentic digital resources, microteaching, feedback, reflection and portfolio-based assessment are systematically integrated. The proposed framework can be used in higher education institutions to improve foreign language teacher education and to support competence-based professional training.